The Golden Hour Trauma Care - Babu, Subbiah Venkatesh (Indian Journal of Neurotrauma, 2021)
Globally the road accidents had become a great burden and claiming lot of precious lives today. However, the initial treatment within the first hour of the injury indeed had proven the high chance of survival after the trauma. This article updates and signifies the systematic emergency approach and current principles in saving lives after injury.
Keywords: prehospital; trauma; injury; golden hour